COVID−19, Anti-NMDA Receptor Encephalitis and MicroRNA - Wang, Hsiuying (Frontiers in Immunology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has had a huge impact on the world, affecting people's lifestyles, economies, and livelihoods. Recently, with the development of vaccines, the infected cases have decreased. Many case reports revealed that COVID-19 may induce other serious comorbidities such as anti-N-methyl-d-aspartate anti-NMDA (anti-NMDA) receptor encephalitis. Anti-NMDA receptor encephalitis is an acute autoimmune disease that occurs more commonly in women than in men. To explore the association between COVID-19 and anti-NMDA receptor encephalitis, I reviewed the microRNA (miRNA) biomarkers of COVID-19, anti-NMDA receptor encephalitis, or other related diseases from the literature, and then based on these miRNA biomarkers to discuss the relationship between COVID-19 and anti-NMDA receptor encephalitis. miRNAs are small non-coding RNAs that play important roles in cell differentiation, development, cell cycle regulation, and apoptosis. miRNAs have been used as biological biomarkers for many diseases. The results in this study reveal that the relationship between anti-NMDA receptor encephalitis and COVID-19 infection or COVID-19 vaccines cannot be excluded, but the risk that COVID-19 triggers the anti-NMDA receptor encephalitis is not high.